A local rehabilitation service for children with hearing loss - Gaziz Sh. Tufatulin; Inna V. Koroleva (Наука и инновации в медицине, 2021)
Objectives to discuss the issues of inter-disciplinary cooperation for improvement the pediatric audiological care using modern technologies for hearing restoration.